2021
DOI: 10.3390/ijerph18042103
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Lockdown and Mental Health in a Sample Population in Spain: The Role of Self-Compassion

Abstract: Previous data support that mental health is affected during pandemic and lockdown situations. Yet, little is known about the positive factors that protect mental health during a lockdown. This study analyzed mental health status—particularly emotional problems—and the role of several sociodemographic and clinical variables; it also explored whether there is a positive relationship between self-compassion and better mental health status. A cross-sectional study was carried out in Spain with the participation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
33
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 97 publications
5
33
1
3
Order By: Relevance
“…In our study, perceived stress was associated with poor mental health, which makes sense considering the interrelatedness of these constructs: high levels of stress typically have an adverse effect on the overall mental well-being and vice versa. A university degree also predicted poor mental well-being in our study, which is similar to results from a recent Spanish study that found a relationship between higher education and higher levels of depression [ 14 ]. In other studies, higher socioeconomic status has been associated with better mental well-being and health in general [ 36 , 37 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our study, perceived stress was associated with poor mental health, which makes sense considering the interrelatedness of these constructs: high levels of stress typically have an adverse effect on the overall mental well-being and vice versa. A university degree also predicted poor mental well-being in our study, which is similar to results from a recent Spanish study that found a relationship between higher education and higher levels of depression [ 14 ]. In other studies, higher socioeconomic status has been associated with better mental well-being and health in general [ 36 , 37 ].…”
Section: Discussionsupporting
confidence: 91%
“…In a survey among the general Italian population, respondents reported scores within clinical ranges for overall distress, depression, anxiety and PTSD [ 13 ]. Similarly, a cross-sectional population study in Spain showed that around 30% of the respondents exhibited symptoms within the clinical range of depression, anxiety and stress [ 14 ] Unsafe and poor working conditions of health-care workers, especially in the long-term care sector, makes residents and employees more vulnerable to COVID-19 infection, morbidity and mortality [ 15 ]. In some countries, nursing homes have been severely affected by the pandemic; in May 2020, 53.1% of all COVID-19 related deaths in Belgium and 51% of all COVID-19 related deaths in France occurred in nursing homes [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the sample was composed of volunteers available to be re-selected from a previous study, which may have introduced a selection bias. A further limitation is linked to having investigated only two macro strategies for regulating emotions, instead of explaining more specific modalities that are useful in the management of psychopathology [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The findings of this research show the possibility of suffering from anxiety and depression in a situation of home confinement and justify the creation of health programs to prevent this alteration of psychological health, as well as early detection, follow-up and treatment of the problems generated by isolation in the home in the face of an illness that entails major changes in living and working habits. Certain skills such as self-efficacy and the possibility that increasing self-compassion may be used to promote better mental health in similar situations [35][36][37].…”
Section: Discussionmentioning
confidence: 99%